2020
DOI: 10.1029/2020jd032818
|View full text |Cite
|
Sign up to set email alerts
|

Leader Charges, Currents, Ambient Electric Fields, and Space Charges Along Downward Positive Leader Paths Retrieved From Ground Measurements in Metropolis

Abstract: An approach for retrieving the leader channel charge density, leader current, ambient electric field, and space charge along a leader channel path from ground observations with a complicated ground condition was presented. With this approach, properties of two downward positive leaders (DPL1 and DPL2) struck at high-rise buildings were studied based on electric and optical measurements made on the roof of a 100 m high building in Guangzhou, China. It shows that the leader-produced electric field on the roof of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Physics sign convention for the electric field was used in this paper (upward directed field is positive). It is worth noting that here we present a limited number of cases that are representative of common processes, having in mind uncertainties in input variables, including the input geometry, line charge density (e.g., Gao et al., 2020; Shen et al., 2019) and velocity of leaders (e.g., Campos et al., 2014; Proctor, 1997). An open‐source code with a graphical interface is provided as supporting information.…”
Section: Electric Field Characteristics Of the Considered Scenarios F...mentioning
confidence: 99%
“…Physics sign convention for the electric field was used in this paper (upward directed field is positive). It is worth noting that here we present a limited number of cases that are representative of common processes, having in mind uncertainties in input variables, including the input geometry, line charge density (e.g., Gao et al., 2020; Shen et al., 2019) and velocity of leaders (e.g., Campos et al., 2014; Proctor, 1997). An open‐source code with a graphical interface is provided as supporting information.…”
Section: Electric Field Characteristics Of the Considered Scenarios F...mentioning
confidence: 99%
“…Gao et al. (2020) reported the charge densities of the two dart leaders ranged from 0.4 to 15.2 mC/m. Lalande et al.…”
Section: Results and Analysismentioning
confidence: 99%
“…The model of Kasemir (1960) has historically been referred to as the bidirectional leader model, we will instead refer to it as the equipotential leader model, since the equipotential assumption is the most significant difference between this model and other non-physics-based leader models. A number of studies have used measured field changes to model simple charge configurations along leader channels without considering leader conductivity (Cai et al, 2022;Chen et al, 2013;Gao et al, 2020;Jensen et al, 2023b;Karunarathne et al, 2015;Lu et al, 2011). By contrast relatively few studies have attempted to compare the equipotential model to observed electric field changes associated with lightning (Mazur & Ruhnke, 1993;Pasko, 2014;da Silva & Pasko, 2015), and these studies have been somewhat limited by lack of knowledge of the extent or location of the leader channel.…”
Section: Introductionmentioning
confidence: 99%